Honey–old wine in new bottle: a surgically viable antibacterial and antiinflammatory fixator - Shivabasappa, Shivakumar; Raghupathi, Divakar Sullery; Uday Kumar, Nallakukkala; Ravishankar, Nagaraj; Kotekar, Nalini (International Surgery Journal, 2019)
Background: Skin grafts are used to cover the healing wound, in which adherence of the graft to the wound bed is the important element. Honey has been shown to increase the adherence of skin grafts to wound beds and have antibacterial and anti-inflammatory effects and increase healing rate of wounds. Methods: In a single centre based prospective comparative study from November 2016 to April 2018, 60 patients (in 30 patients graft was fixed with sterilised honey, in 30 patients it was fixed with conventional methods like skin staples/sutures). All patients in two groups were evaluated for area of graft uptake, graft contracture, incidence of hematoma/seroma, mean hospital stay post surgery, post-operative pain, Infection rate and Cost effectiveness. Statistical analysis used are chi-square test, independent t test/ Mann-Whitney test, paired t test/ Wilcoxon test. P<0.05 is considered statistically significant. Results: Although graft uptake was same in both the groups, graft contracture, discharge from graft site and infection rate were less in the honey group. There was no seroma formation in the honey group. Honey significantly reduced postoperative pain (p<0.0001%) and is also cost-effective as the hospital stay was shorter in the honey group (p<0.0001%). Conclusions: Honey has strong adhesive properties, anti-inflammatory action and helps in minimization of scarring, and stimulation of angiogenesis as well as tissue granulation and epithelium growth. It also reduces surgical time for skin graft fixation. Sterilized honey has proven advantage as a skin graft fixator.